Software process selection system based on multicriteria decision making. Issue 2 (3rd August 2020) - Pandey, Prateek; Litoriya, Ratnesh
Abstract: Whatever be the nature of underlying software, the impact of the software development process that was used to create it would remain vital. The objective of this paper is to provide a process selection framework for the software development firm's engineers and managers, looking to identify the proper way to build software to run on a mobile, web, or desktop. The motivation behind this work comes from the fact that the applications that fall in one of the above three categories can be significantly different in terms of scale, UI, and memory requirements, time to market, and other characteristics. Software development that needs to be completed in a challenging timeframe has to resort to principles and values as declared in Agile Manifesto. The availability of various agile methodologies has made the project managers often stuck when selecting the most suitable one. The proposed agile process identification system addresses this dilemma of engineering fraternity using a fuzzy variant of a popular multiple‐criteria decision‐making (MCDM) technique called the analytic hierarchy process (AHP). The proposed system is validated through a primary dataset generated as a result of the development of 20 software projects. The results are encouraging enough with a probability of true identification close to 88%.